The level of administrative communication in the Syrian Arab Basketball Federation (Journal of Hama University, 2026)
The research aims to identify the reality of administrative communication in the Syrian Arab Basketball Federation. The researcher used the descriptive analytical approach due to its suitability to the nature of the study. A comprehensive enumeration method was used in selecting the sample, which consisted of (73) administrators in the Syrian Arab Basketball Federation, in addition to its affiliated committees and subcommittees The questionnaire was used as a research tool and consisted of four axes: administrative communication methods, administrative communication skills, and administrative communication characteristics. The data were processed using the statistical program (SPSS), and the most prominent results of the study were The level of administrative communication in the Syrian Arab Basketball Federation is high. There are no differences in the level of administrative communication among members of the Syrian Arab Basketball Federation depending on the variable of years of experience
Keywords: : Administrative communication; basketball; Syrian basketball federation